Evaluation of fluorine‐mediated intermolecular interactions in tetrafluorinated tetrahydroisoquinoline derivatives: synthesis and computational studies. Issue 4 (13th July 2020) - Singla, Labhini; Yadav, Hare Ram; Roy Choudhury, Angshuman
Abstract : The importance of fluorine‐mediated interactions in the crystal structures of a series of tetra‐fluorinated tetrahydroisoquinoline derivatives through structural and computational analysis is presented. Abstract : Intermolecular interactions involving the aromatic C—F group in the absence of other strong hydrogen bond acceptors is the theme of this article. Weak interactions involving fluorine are known to generate various supramolecular synthons, thereby altering the crystal structures of small organic molecules. It is demonstrated that the weak interactions involving organic fluorine play a major role in directing crystal packing of highly flexible organic molecules like diphenyl tetrahydroisoquinolines reported herein. The intramolecular C—H…F hydrogen bonds are found to be significant in controlling the molecular conformation in specific cases wheras the intermolecular interactions involving the C—F groups result in a wide range of supramolecular synthons involving C—H…F and C—F…F—C interactions. The interactions are studied computationally to provide insight into their energies and the topology of the interactions is studied using Atoms in Molecules. C—H…F—C interactions are found to be quite stabilizing in nature with the stabilization energy of −13.9 kcal mol −1 .